POSTURAL BALANCE PROGRAM: VARIABLES RELATED TO FALLS IN ELDERLY - Andréa Kruger Gonçalves; Eduardo Hauser; Valéria Feijó Martins; Vanessa Dias Possamai; Eliane Mattana Griebler; Eliane Jost Blessmann; Adriane Ribeiro Teixeira (Journal of Physical Education)
ABSTRACT The aim of this study was to analyze the effects of a balanced program for preventing falls in the elderly. The sample consisted of 17 subjects (age: 75.73 ± 8.57). The tests used were one foot (AU), Timed Up and Go (TUG), functional reach (AF), strength (IMF) and flexibility of the lower limbs (FLEXMI) of Rikli and 19 Jones (1999) protocol, FES-I questionnaire. For data analysis we used the comparative statistics with the Wilcoxon test (p = 0.05) between pre and post-test. For the analysis of the classification of balance tests we used distribution calculations (frequency and percentage). There was no statistically significant change between the pre and post-training in the variables AU, TUG and FLEXMI. The classification of the results showed improved post-test, showing a tendency to improve balance after training and helping to prevent falls